HISTORY AND PROSPECTS OF MELILOT BREEDING IN TRANSBAIKALIA - V. P. Makarov; G. M. Andrusova (Труды по прикладной ботанике, генетике и селекции)
The article presents the results of research work on melilot (Melilotus Mill.) breeding in Transbaikalia in the period from 1939 to the present. The purpose has been to outline the prospects for further breeding of melilot in Transbaikalia. This work has been accomplished involving literary sources, research reports and publications of the authors, the results of field studies, herbarium collections of various institutions, reports of scientific institutes in Transbaikalia. The article contains the data on distribution of Melilotus spp. in Transbaikalia, the history of their breeding, and information about melilot accessions promising for further breeding.